Modelo de sistema de costos “ABC” para las pymes de la madera del cantón Latacunga provincia de Cotopaxi en el periodo julio- diciembre del 2011 - Quevedo Villamarin, Martha Mercedes (2013)
This work of research, was raised with the aim of producing a cost "ABC" system model for PYMES in the wood of the Canton in Latacunga, Cotopaxi province which will serve as a guide for the correct assignment of all the costs that are part of the process facilitating the best administration decision that will improve the economic development of these companies. This study allowed knowing the lack of guidance to control of a cost system causing that production takes empirically what hinders the recognition of processes that do not generate value to the finished product. This work was carried out by applying the theoretical method allowed us to collect information from bibliographic sources. Also used in inductive-deductive methods since it was a situational diagnosis of this sector to know the current reality of PYMES. Finally put at disposal of managers in this sector a cost ABC system model it contains actual data since it was applied to one of them as it is MADECOR and which will later serve as an instruction applicable to companies that are engaged in this activity.